(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
What I will present, in this visual essay, are images of my house/studio in Goiânia, which I also started calling Lapidarium. With them, I intend to generate material visuality of my relationship with the studio, of what I bring to it, of what I select to produce works of art, of the tools I use to do so and of the space I occupy. Therefore, the focus here is not a specific work but the everyday conjectures of my artistic production and the space/time necessary for the works to happen. I bring visual excerpts of the preparation, apparatus and daily organization of my artistic work. Using a text by author Luiz Alberto Warat (2004), which says something similar to what I have always done in my studio, I will continue this essay with reflections on what he says and images from my studio.